Evaluation of oxidative stress response in endoscopic and Lichtenstein hernia repair: A randomized control study - Rahul Saini; Lovenish Bains; Niladhar Shankarrao Hadke; Bidhan Chandra Koner; Rajdeep Singh; Pawan Lal (International Journal of Abdominal Wall and Hernia Surgery, 2020)
BACKGROUND: The extent of inflammatory and oxidative stress response varies with different surgical procedures. The aim of the study was to compare the same between total extraperitoneal repair and Lichtenstein repair for inguinal hernia. MATERIALS AND METHODS: Men, aged 18–60 years with an ASA score of 1, presenting with primary unilateral indirect inguinal hernia were randomized to total extraperitoneal repair (TEP) and Lichtenstein repair. Blood samples were collected an evening before surgery and postoperatively at 2, 24, and 48 h to compare the levels of highly sensitive C-reactive protein (hs-CRP), malondialdehyde (MDA), and neutrophil: lymphocyte ratio between the two modes of repair. RESULTS: Both modalities of repair cause a significant inflammatory response in the body (P < 0.05). The rise in the level of serum hs-CRP and neutrophil: lymphocyte ratio was significantly more in the open surgery group as compared to the TEP group at 2, 24, and 48 h postoperatively (P < 0.05). The levels of serum MDA were distinctively higher (P = 0.042) only at 2 h after surgery in the former group. CONCLUSION: Endoscopic repair is associated with a significantly lesser oxidative response than Lichtenstein repair based on this study (P < 0.05). Although this might be one of the bases for lesser postoperative pain and earlier return to activity in TEP repair, more randomized studies are required to draw a definitive conclusion.